2018
DOI: 10.4034/pboci.2018.181.61
|View full text |Cite
|
Sign up to set email alerts
|

The Regulation of Services in Secondary Oral Health Care in Brazil

Abstract: Objective: To analyze the regulation of access to Centers for Dental Specialties (CEO) in the 1 st cycle of Program for Improving Access and Quality of Centers for Dental Specialties (PMAQ-CEO), specifically the waiting time for the first consultation in association with socioeconomic and demographic factors of users and the characteristics of services. Material and Methods: The quantitative database of the 1 st cycle PMAQ-CEO external evaluation was used, with question directed to the CEO user (Module III -3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The data used in our study corresponded to interviews with CEO managers and dentists 3 . Data from the second phase of the PMAQ ‐ CEO were provided by the Ministry of Health (http://aps.saude.gov.br/ape/pmaq/ciclo2ceo/).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The data used in our study corresponded to interviews with CEO managers and dentists 3 . Data from the second phase of the PMAQ ‐ CEO were provided by the Ministry of Health (http://aps.saude.gov.br/ape/pmaq/ciclo2ceo/).…”
Section: Methodsmentioning
confidence: 99%
“…The secondary database from the second phase of the PMAQ-CEO's External Assessment was used, which consisted of an in loco survey that analysed the The data used in our study corresponded to interviews with CEO managers and dentists. 3 Data from the second phase of the PMAQ-CEO were provided by the Ministry of Health (http://aps.saude.gov. br/ape/pmaq/ciclo 2ceo/).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a lack of studies evaluating specialized oral health care in Brazil [4,10,12]. Previously published studies reported the results of the first cycle of the PMAQ-CEO [2,8,10,11,[13][14][15][16][17]; however, data from the second cycle are still poorly known. Thus, the aim of the present study was to analyze specialized dental care through access, demand and the work process provided by the CEO's, using secondary data from the cycles of the PMAQ-CEO.…”
Section: Introductionmentioning
confidence: 99%